Comparison Between Reiter Protein Compelment Fixation Test and Fluorescent Treponemal Antibody Test for Syphilis - OHARA, Tsuneki; TAKUMI, Kenji (Journal of the Japanese Association for Infectious Diseases, 1965)
Biologic false positive (BFP) is said to be unavoidable because of the unspecific antigen of Cardiolipin reaction (CL-R), a standard method of serological diagnosis for syphilis. On the other hand, RPCF and FTA test are highly appreciated due to their high specifity and easy practicability. In this report, BFP of CL-R and coincidence between RPCF and FTA test were studied by comparing CL-R (Ogata, glass-slide and agglutination methods), RPCF and FTA test performed on 1073 syphilitic and non-syphilitic sera. The results were as follows: RPCF and FTA test were coindicently negatice in 8.3% of 291 CL-R positive (in all the 3 methods) sera out of 348 syphilitic ones. Glass slide method known as most sensitive among the 3 CL-R methods was positive in 4.1% of 725 non-syphilitic sera, RPCF being positive in 6.6% of them. Though RPCF and FTA test were coincidently positive in 91.9% of 348 syphilitic sera, FTA test demonstrated in nonsyphilitic sera 3.3% positive rate, RPCF test 6.6%, i.e. twice as high as the former. Because of lacking clinical histories of the sera investigated, the BFP of RPCF test could not be judged directly from the data mentioned above. However, unspecifity of the RPCF antigen used in this experiment did not seem to be denied. As for the FTA test, no definite data proving ist high specifity could be obtained. Compared, however, with the other ones, FTA test appeared to be most reliable as a standard method.